TutoriVR: A Video-Based Tutorial System for Design Applications in Virtual Reality - Kumaravel, Balasaravanan Thoravi; Nguyen, Cuong; DiVerdi, Stephen; Hartmann, Björn (CHI '19: Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems, 2019)
Virtual Reality painting is a form of 3D-painting done in a Virtual Reality (VR) space. Being a relatively new kind of art form, there is a growing interest within the creative practices community to learn it. Currently, most users learn using community posted 2D-videos on the internet, which are a screencast recording of the painting process by an instructor. While such an approach may suffice for teaching 2D-software tools, these videos by themselves fail in delivering crucial details that required by the user to understand actions in a VR space. We conduct a formative study to identify challenges faced by users in learning to VR-paint using such video-based tutorials. Informed by results of this study, we develop a VR-embedded tutorial system that supplements video tutorials with 3D and contextual aids directly in the user's VR environment. An exploratory evaluation showed users were positive about the system and were able to use the proposed system to recreate painting tasks in VR.